Encrusted Uropathy: A Comprehensive Overview—To the Bottom of the Crust - Van de Perre, Els; Reichman, Gina; De Geyter, Deborah; Geers, Caroline; Wissing, Karl M.; Letavernier, Emmanuel (Frontiers in Medicine, 2021)
Encrusted uropathy is a rare subacute to chronic inflammatory disorder caused by infection with urease-producing bacteria, mainly Corynebacterium urealyticum. The disorder is characterized by urothelial deposition of struvite and carbonated apatite, resulting in encrustations and ulceronecrotic inflammation of the urothelium and surrounding tissues. Most commonly, encrusted uropathy is encountered in patients with predisposing conditions. The disease remains underdiagnosed. High urinary pH and negative conventional urine cultures should raise suspicion of the diagnosis. Prognosis is dependent on timely diagnosis and treatment instalment, which consists of urological removal of encrustations in combination with urinary acidification and long-term antibiotic therapy.